Building a Halal Ecosystem Through Sharia Business Education and MSME Mentoring - Muhammad Bekti Hendrie Anto; Heri Sudarsono; Abdurrahman, Zahron; Kinanthi Putri Ardiami; Achmad Rizal (FEBI UIN Sunan Kalijaga Yogyakarta, 2025)
The concepts of halal and thayyib serve as fundamental pillars of Islamic-based business, encompassing not only the products consumed but also the entire underlying business process. Micro, Small, and Medium Enterprises (MSMEs) located around the Faculty of Business and Economics (FBE), Universitas Islam Indonesia (UII), particularly in Dero Hamlet, Ngringin, demonstrate considerable potential for developing Sharia-compliant business practices. However, limited knowledge regarding the concepts of halal, Islamic business management, and the halal certification process remains a major constraint. This community service program was designed to enhance literacy and practical implementation of halal business principles through the Sharia Business School for MSMEs, which integrates educational sessions, training activities, and halal certification assistance. The methodology comprised three main stages: assessment, training, and evaluation. The results indicate an improvement in participants’ understanding of the Islamic business cycle and a heightened awareness of the importance of halal certification. This initiative is expected to serve as a sustainable model for community empowerment, contributing to the establishment of a Halalan Thayyiban business ecosystem within the FBE UII environment.